Caffeinated sports drink: Ergogenic effects and possible mechanisms - Cureton, K. J.; Warren, G. L; Millard-Stafford, M. L.; Wingo, J. E.; Trilk, J.; Buyckx, M. (International Journal of Sport Nutrition and Exercise Metabolism, 2007)
This double-blind experiment examined the effects of a caffeinated sports drink during prolonged cycling in a warm environment. Sixteen highly trained cyclists completed 3 trials: placebo, carbohydrate-electrolyte sports drink (CES), and caffeinated sports drink (CES+CAF). Subjects cycled for 135 min, alternating between 60% and 75% VO2max every 15 min for the first 120 min, followed by a 15-min performance ride. Maximal voluntary (MVC) and electrically evoked contractile properties of the knee extensors were measured before and after cycling. Work completed during the performance ride was 15-23% greater for CES+CAF than for the other beverages. Ratings of perceived exertion were lower with CES+CAF than with placebo and CES. After cycling, the MVC strength loss was two-thirds less for CES+CAF than for the other beverages (5% vs. 15%). Data from the interpolated-twitch technique indicated that attenuated strength loss with CES+CAF was explained by reduced intrinsic muscle fatigue.